Studi Eksploratif Kualitas Hidup Kerja Dalam Meningkatkan Kinerja Karyawan PT Bank Sumut Syariah Kota Medan - Vidairotul Hamdiah; Saparuddin Siregar; Tuti Anggraini (Universitas KH. Abdul Chalim Mojokerto, 2025)
The decline in employee performance at the Medan Syariah Branch and the Medan Ringroad Syariah Branch of PT Bank Sumut Syariah, Medan, has had a serious impact on the organization’s target achievement. This condition is suspected to be related to suboptimal Quality of Work Life (QWL), such as an imbalanced workload, limited participation in decision-making, lack of transparency in the reward system, and minimal attention to mental health. In the context of Islamic banking, this issue is also closely tied to the application of Islamic values such as justice (‘adl), trustworthiness (amanah), consultation (shura), and excellence (ihsan). This study aims to explore and analyze the influence of QWL on employee performance using a mixed-method sequential exploratory design. The qualitative phase was conducted through in-depth interviews with eight informants, revealing that although restructuring has accelerated digitalization, it has also increased work pressure. Participation is still perceived as symbolic, the reward system is considered unfair, and the work environment lacks attention to psychological aspects. The quantitative results, obtained through questionnaires distributed to 104 respondents, show that the four variables work restructuring, job participation, reward system, and work environment have a positive and significant influence on performance, with an R² value of 0.707. The synthesis of both approaches confirms that a high quality of work life, both technically and spiritually, can enhance employee performance. The consistent application of Islamic values in organizational management can strengthen employees’ motivation, loyalty, and professionalism. This study recommends comprehensive, fair, and value-based QWL management as a strategic approach to improving performance in Islamic banking.